Diuretic activity of the flavonoid pinostrobin previously identified from the species Renealmia alpinia (2023)
ABSTRACT: Renealmia alpinia is a plant traditionally employed as antiophidic, pain reliever, antipyretic, and antiemetic. Its main metabolites are flavonoids, with pinostrobin as the most abundant compound of this plant species. In this study, we determined the diuretic activity of pinostrobin, previously identified from the species Renealmia alpinia in normal mice. The evaluation of the diuretic activity of the flavonoid pinostrobin was carried out at doses of 5, 10, and 20 mg/kg of body weight. The diuretic activity was evaluated using the Kau et al. (1984) method with modifications made by Benjumea et al. (2005), using mice instead of rats. Metabolic cages equipped with graduated cylinders were used to measure the volume of urine excretion at 2, 4, and 6 hours. At 6 hours, pH and conductivity were measured, and the concentration of excreted sodium, potassium, magnesium, and calcium ions was estimated by ion chromatography. Creatinine, albumin, blood urea nitrogen, and urea of mice blood were analyzed. There was an increase of 32% and 38% at a dose of 10 and 20 mg/kg, respectively, in the urinary excretion of water by pinostrobin, an elimination of sodium concentration similar to furosemide at 5 and 10 mg/kg, An increase in potassium concentration of 52% at 10 mg/kg and a higher magnesium excretion of 85% at 5 mg/kg, were statistically significant compared to furosemide. Pinostrobin showed a diuretic effect increasing the volume of urinary excretion in mice and excretion of sodium, potassium, magnesium, and calcium ions, with a possible mechanism in the loop of Henle.